If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 3) + 3x = 0 Reorder the terms: 2(3 + 5x) + 3x = 0 (3 * 2 + 5x * 2) + 3x = 0 (6 + 10x) + 3x = 0 Combine like terms: 10x + 3x = 13x 6 + 13x = 0 Solving 6 + 13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 13x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 13x = 0 + -6 13x = 0 + -6 Combine like terms: 0 + -6 = -6 13x = -6 Divide each side by '13'. x = -0.4615384615 Simplifying x = -0.4615384615
| 3x-y+33=0 | | 4.6r-3.2=3.2r-3.9 | | M^0n^6=0 | | 3x+100=-5x+900 | | 7x+28=70 | | 7x+14=2x+18 | | 14-18=40 | | 54+18x= | | 5.6+2.5=.9r | | 4+10=72 | | 16=-16t^2+16t+32 | | -15n+17=-14n-2 | | 7.8=23.4 | | 5(9.5-8h)=-20.5 | | 18-22=120 | | 4-11=120 | | 20a^2-15a= | | 3k+4+6k=-8+8k | | 3-8=35 | | m-4=22 | | 5+5+5=3x | | 17x-7+20x+15x+12x-17=360 | | 4ax-3b=b+20 | | -8d=80 | | 2-u=78 | | 7-9[7-(7y-4)]=0 | | x^4-2x^3+6x^2+8x-27=0 | | 11-18=63 | | -59+-2x=21-7x | | 4+3n=61 | | -[7z-(12z+4)]=4+(4z+1) | | (7p+2)3+8p= |